UNRAVELING THE EFFECTS OF ECONOMIC POLICY UNCERTAINTY: STRATEGIC CONTRIBUTIONS OF MARKETING, OPERATIONS, AND RESEARCH AND DEVELOPMENT - Aripin, Zaenal; Susanto, Bambang; Sikki, Nurhaeni (KRIEZ ACADEMY : Journal of development and community service, 2024)
Uncertainty in economic policy has become a significant challenge for companies in various industrial sectors. In this research, we disentangle the influence of economic policy uncertainty on the strategic contribution of marketing, operations, research and development in the modern business context. Through a qualitative approach, we explore how companies face the challenges of economic uncertainty and the strategies they adopt to overcome its negative impacts. In a marketing context, we highlight the importance of a deep understanding of changes in consumer behavior and flexibility in reaching market segments that still have strong purchasing power. On the operational side, we discuss how companies are managing risks associated with supply chain fluctuations and production costs through stronger collaboration and the adoption of innovative technologies. In terms of research and development, we highlight the importance of intelligent resource allocation, collaboration with external partners, use of data analytics, and product development that can improve a company's operational efficiency. By analyzing our findings, we conclude that companies need to take a proactive and innovative approach in managing economic policy uncertainty to ensure their long-term business growth and sustainability.